Sleep Characteristics and Influencing Factors of Sleep Quality in Patients With Inflammatory Bowel Disease-Peripheral Arthritis - Zhang, Yin; Pi, Bin; Xu, Xianlin; Li, Ying; Chen, Xiangfan; Yang, Ningxi; Li, Xiaoyan (Frontiers in Medicine, 2020)
Background: Patients with inflammatory bowel disease-peripheral arthritis (IBD-PA) often accompany by sleep problems, but few studies have used polysomnography to investigate the objective sleep characteristics of IBD-PA. Methods: Patients in IBD-PA group, inflammatory bowel disease (IBD) group, healthy control (HC) group were examined by polysomnography (PSG) and the sleep characteristics were compared. PSG and Pittsburgh Sleep Quality Scale (PSQI) indices were compared between active and remission IBD-PA patients. The correlation between disease activity and sleep quality in IBD-PA patients was analyzed. The influencing factors of sleep efficiency of IBD-PA patients were analyzed. Results: The total sleep time (TST), rapid-eye-movement sleep (REM) time, slow wave sleep (S3 + S4) and sleep efficiency (SE) in the IBD-PA group were significantly less than those in the HC group and IBD group (P < 0.05), while the number and time of wake after sleep onset (WASO) and sleep latency (SL) were significantly longer than those in the HC group and IBD group (P < 0.05). To IBD-PA patients, the disease activity was negatively related to sleep quality. There was a significant difference in SE, the number of WASO, S1, S3+S4 of PSG, as well as the PSQI total score between active and remission patients. Abdominal pain, joint pain, depression, and C-reactive protein were the influencing factors of sleep efficiency. Conclusions: The sleep quality of patients with IBD was poor than the control group, and that of patients with IBD-PA was even worse. Therefore, sleep management should be included in IBD management.